Quality of Life of Parents of Children with Atopic Dermatitis - Joanna Marciniak; Adam Reich; Jacek C. Szepietowski (Medical Journals Sweden, 2017)
Atopic dermatitis (AD) is the most common chronic dermatitis in children. The influence of AD on quality of life of parents of children with AD was studied using the Family Dermatology Life Quality Index (FDLQI). Fifty children with AD were included in the study (age range 2-24 months) together with their parents. Children's AD was found to influence the quality of life of both parents; however, it had a more significant influence on quality of life of mothers than that of fathers (mean FDLQI: 17.1 ± 5.3 vs. 14.7 ± 5.8 points; p < 0.001). Due to the children's AD, mothers spent more time caring for them and carried out more household duties. Childhood AD had a greater impact on quality of life of fathers through influence on their work or education. The influence of AD on the quality of life of family members is significant, and this should be taken into account in the therapeutic process.